Clinical characteristics and long-term clinical course of patients with Brugada syndrome without previous cardiac arrest: a multiparametric risk stratification approach. Issue 12 (22nd October 2019) - Letsas, Konstantinos P; Bazoukis, George; Efremidis, Michael; Georgopoulos, Stamatis; Korantzopoulos, Panagiotis; Fragakis, Nikolaos; Asvestas, Dimitrios; Vlachos, Konstantinos; Saplaouras, Athanasios; Sakellaropoulou, Antigoni; Mililis, Panagiotis; Strempelas, Panagiotis; et al.
Abstract: Aims: Risk stratification in Brugada syndrome (BrS) still represents an unsettled issue. In this multicentre study, we aimed to evaluate the clinical characteristics and the long-term clinical course of patients with BrS. Methods and results: A total of 111 consecutive patients (86 males; aged 45.3 ± 13.3 years) diagnosed with BrS were included and followed-up in a prospective fashion. Thirty-seven patients (33.3%) were symptomatic at enrolment (arrhythmic syncope). An electrophysiological study (EPS) was performed in 59 patients (53.2%), and ventricular arrhythmias were induced in 32 (54.2%). A cardioverter defibrillator was implanted in 34 cases (30.6%). During a mean follow-up period of 4.6 ± 3.5 years, appropriate device therapies occurred in seven patients. Event-free survival analysis (log-rank test) showed that spontaneous type-1 electrocardiogram pattern ( P = 0.008), symptoms at presentation (syncope) ( P = 0.012), family history of sudden cardiac death ( P < 0.001), positive EPS ( P = 0.024), fragmented QRS ( P = 0.004), and QRS duration in lead V2 > 113 ms ( P < 0.001) are predictors of future arrhythmic events. Event rates were 0%, 4%, and 60% among patients with 0–1 risk factor, 2–3 risk factors, and 4–5 risk factors, respectively ( P < 0.001). Current multiparametric score models exhibit an excellent negative predictive value and perform well in risk stratification of BrS patients. Conclusions: Multiparametric models including common risk factors appear to provide better risk stratification of BrS patients than single factors alone.